Respiratory Outcome after Preterm Birth: A Long and Difficult Journey - Priante, Elena; Moschino, Laura; Mardegan, Veronica; Manzoni, Paolo; Salvadori, Sabrina; Baraldi, Eugenio (American Journal of Perinatology, 2016)
Despite notable advances in the survival and management of preterm infants in recent decades, chronic lung disease remains a common complication. Approximately one in three infants born preterm (< 32 weeks of gestation) are hospitalized with respiratory problems (mainly due to infections) in their first 2 years of life, and the risk of childhood wheezing is three times higher in this population. By comparison with infants born at term, there seems to be a higher incidence of respiratory morbidity in those born preterm, even in the absence of bronchopulmonary dysplasia (BPD) and in late-preterm babies. Although long-term follow-up data are still not collected systematically, there is evidence of preterm infants' respiratory symptoms, lung function impairments, and radiological abnormalities, tending to persist throughout childhood and into early adulthood. Respiratory conditions associated with preterm birth are often diagnosed and treated as asthma, but the pathophysiological patterns of BPD and asthma are very different. Future research should focus on characterizing preterm infants' pathological pulmonary features by gestational age at birth, and presence or absence of BPD. Improving our current knowledge of the respiratory disorder associated with prematurity might hopefully prompt targeted follow-up protocols, and novel prevention strategies and treatment approaches.
Keywords: bronchopulmonary dysplasia; preterm; chronic respiratory disease; lung function